Studies on serum level of some trace elements in oculocutaneous albinism subjects in Owerri metropolis - Constance, Nwadike; Ijeoma, Nosiri Chidi; Magnus, Nsonwu; Chidimma, Akanazu; Nkeiruka, Olly-Alawuba; Catherine, Onyejekwe; Kaosisochukwu, Catherine; Chimaraoke, Onyeabo (International Multidisciplinary Research Journal, 2020)
Studies on serum level of some trace elements in oculocutaneous albinism subject in Owerri metropolis was carried out using standard methods. Sixty (60) volunteer subjects made of 30 male and 30 female were used for the study. With the help of syringes, their sera were obtained from their blood samples and used for trace element analysis. Observed results revealed significant (p<0.05) decrease in levels of copper and zinc in male and female oculocutaneous albinism subjects against the control. The mean values for copper and zinc in both male and female also showed significant (p<0.05) reduction when compared to the control. The observed decreased in copper could influence tyrosinase and subsequently melanin production. There is need to investigate the relationship of the pigmentation disorder with other trace elements that were not considered in the present study. This study has revealed the serum level of some trace elements in oculocutaneous albinism subject in Owerri metropolis.